Photosynthetic recovery in drought‐rehydrated grapevines is associated with high demand from the sinks, maximizing the fruit‐oriented performance. (28th October 2022) - Patono, Davide L.; Said‐Pullicino, Daniel; Eloi Alcatrāo, Leandro; Firbus, Andrea; Ivaldi, Giorgio; Chitarra, Walter; Ferrandino, Alessandra; Ricauda Aimonino, Davide; Celi, Luisella; Gambino, Giorgio; Perrone, Irene; Lovisolo, Claudio
SUMMARY: To understand how grapevine sinks compete with each other during water stress and subsequent rehydration, carbon (C) allocation patterns in drought‐rehydrated vines (REC) at the beginning of fruit ripening were compared with control vines maintained under drought (WS) or fully irrigated (WW). In the 30 days following rehydration, the quantity and distribution of newly fixed C between leaves, roots and fruits was evaluated through 13 CO2 pulse‐labeling and stable isotope ratio mass spectrometry. REC plants diverted the same percentage of fixed C towards the berries as the WS plants, although the percentage was higher than that of WW plants. Net photosynthesis (measured simultaneously with root respiration in a multichamber system for analysis of gas exchange above‐ and below‐ground) was approximately two‐fold greater in REC compared to WS treatment, and comparable or even higher than in WW plants. Maximizing C assimilation and delivery in REC plants led to a significantly higher amount of newly fixed C compared to both control treatments, already 2 days after rehydration in root, and 2 days later in the berries, in line with the expression of genes responsible for sugar metabolism. In REC plants, the increase in C assimilation was able to support the requests of the sinks during fruit ripening, without affecting the reserves, as was the case in WS. These mechanisms clarify what is experienced in fruit crops, when occasional rain or irrigation events are more effective in determining sugar delivery towards fruits, rather than constant and satisfactory water availabilities. Significance Statement: In the rehydration phases following a period of drought, the strength of fruit carbon sinks inherited from the previous period of stress persists in grapevines, combined with a decisive photosynthetic recovery. These phases become the key moments in the life of fruit plants, especially if they coincide with the ripening phase of the fruit.